2023
DOI: 10.1002/ctm2.1155
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex immunofluorescence and single‐cell transcriptomic profiling reveal the spatial cell interaction networks in the non‐small cell lung cancer microenvironment

Abstract: Background Conventional immunohistochemistry technologies were limited by the inability to simultaneously detect multiple markers and the lack of identifying spatial relationships among cells, hindering understanding of the biological processes in cancer immunology. Methods Tissue slices of primary tumours from 553 IA∼IIIB non‐small cell lung cancer (NSCLC) cases were stained by multiplex immunofluorescence (mIF) assay for 10 markers, including CD4, CD38, CD20, FOXP3, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 77 publications
(170 reference statements)
0
23
0
Order By: Relevance
“…By canonical cell markers, nine major cell clusters of tumor cells and tumor‐infiltrated immune cells were detected. The histochemistry score 23 indicated a greater abundance of PDL1+ cells in TME of high inflammation group (Figure 4C). The expression of PDL1 was then used for subclass division of tumor cells and immune cells.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…By canonical cell markers, nine major cell clusters of tumor cells and tumor‐infiltrated immune cells were detected. The histochemistry score 23 indicated a greater abundance of PDL1+ cells in TME of high inflammation group (Figure 4C). The expression of PDL1 was then used for subclass division of tumor cells and immune cells.…”
Section: Resultsmentioning
confidence: 94%
“…Multiplex immunofluorescence analysis was performed using previously described methods 23,24 . The Opal 7‐Color Manual IHC Kit (PerkinElmer, NEL811001KT) was used to stain slides from formalin‐fixed paraffin‐embedded NSCLC tissues.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Peng et al. have shown that N1‐like neutrophils could enhance the activation of T and B cells in NSCLC, while nearby M2‐like macrophages exhibited inhibitory effects 46 . Leader et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that a higher density of CD8+ T cells neighboring CD8- T cells or regulatory T cells was associated with better prognosis of patients with NSCLC, indicating the potential significance of the CD8+ T cells limited in certain spatial scale [ 10 , 11 ]. Additionally, Peng et al provided a novel insight to decode spatial information of immune cell, through variables based on the intercellular distance reflecting the level of interaction [ 12 ]. Therefore, a comprehensive decipherment of the spatial structure is necessary for intratumoral CD8+ T cells in NSCLC.…”
Section: Introductionmentioning
confidence: 99%